PEGARUH PROFITABILITAS, UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL - Vera Melia Suci; Erny Rachmawati (Media Ekonomi, 2016)
This study is to analize the effects of profitability, firm size, sales growth, and assets structure to the capital structure among property and real estate companies listed in the Indonesian Stock Exchange in the period of 2011-2014. The sample were selected based on purposive sampling technique. To the total number of 43 different companies with a fouryear observation time, so the samples would be 172 observations. The study used a secundary data in the for of financial site Indonesian Stock Market (BEI), such as www.idx.co.id.The result of the research showed that profitability does not affect to the capital structure, The firm size has a positive affect to the capital struture. The last two variables growth sales and assets structure have any negative effect to the capital structure. Keyword: capital strucrure, profitability, firm size, sales growth, assets structure.